PWE-114 The Ibd-control Questionnaire: Multi-centre Validation Plus Evaluation In Routine Care. (9th June 2014) - Gledhill, T; Brown, E; Collins, B; Subramanian, S; Bassi, A; Bodger, K
Abstract : Introduction: Routine capture of reliable, patient-centred health status measures for IBD has not become part of standard practice. The IBD-Control questionnaire is a short (13 item), generic patient-reported outcome measure which we developed to support routine care. 1 Methods: To further define performance in varied settings, we undertook: (A) A prospective study at an inner city teaching hospital and a DGH, to show reproducibility of psychometric properties. Clinic patients completed IBD-Control and the local IBD team recorded activity index, global physician assessment and treatment. (B) A prospective endoscopic study, with IBD-Control prior to endoscopy and Mayo score of mucosa. IBD teams were blinded to questionnaires. (C) A service evaluation in our unit, auditing implementation of IBD-Control to support a new virtual (telephone) clinic – a case study on integrating PROMs into routine care. Results: 113 IBD-Control questionnaires returned to date. Patients: Age, mean [sd]: 50 [16] yrs; Female: 54%; UC: 73%; Disease duration, mean [sd]: 7.5 [7.7] yrs. Global Physician Assessment: Inactive 48.3%; Mild 41.3%; Moderate 10.3%; Severe 0%. Summary scores, mean [sd]: IBD-Control-8 (range: 0–16): 11.7 [5.2]; IBD-Control-VAS (range: 0–100): 73.5 [76.1]. Psychometric properties: Completion rate : 93–94% per item; Strong correlation between the 2 summary scores: IBD-Control-8 vs IBD-Control-VAS, r = 0.83; Validity of summary scores, IBD-Control-8 [IBD-Control-VAS]: (1) Simple Clinical Colitis Activity Index, r = –0.77 [–0.72]; (2) Harvey Bradshaw Index, r = –0.91 [–0.78] (3) Mayo Score, r = –0.64 [–0.69]; (3) Global Physician Assessment, mean scores differed significantly across categories for both scores (inactive > mild > moderate; p < 0.01, ANOVA). Service Evaluation: 64 'delayed follow-up or DNA' patients invited for postal return of PROM then 4–6 wk review, with 59% return rate ('active disease' indicated in 10%). Telephone consultation in 63%. Unplanned care occurred in 2 respondents within 30 days, both with IBD-Control indicative of active disease. Conclusion: IBD-Control has strong measurement properties and is easy to administer. Our experience of integrating IBD-Control into non-face-to-face follow-up clinics suggests that using a validated PROM to support care is acceptable to patients and achievable. Reference: Bodger K et al . Development and validation of a rapid, generic measure of disease control from the patient's perspective: the IBD-Control questionnaire. Gut 2013;published online October 9:2013 [ahead of print] Disclosure of Interest: None Declared.